Sirt6 prevents the age-related decline of H 2 S through the control of one-carbon metabolism - Noga Touitou; Liat Nahum; Sarit Feldman-Trabelsi; Matan Y. Avivi; Miguel A. Aon; Shoshana Naiman; Moran Rathaus; Asaf A. Gertler; Asael Roichman; Lia Berkman Dvir; Michel Bernier; Nirad Banskota; et al. (Proceedings of the National Academy of Sciences, 2025)
Mice overexpressing Sirt6 or fed a caloric restriction (CR) diet live longer with improved health. CR increases Sirt6 levels, and its beneficial effects are mediated by the gasotransmitter H 2 S, a one-carbon pathway product. Yet, the role of this pathway in Sirt6-regulated longevity remains elusive. Here, we show that Sirt6 controls hepatic one-carbon metabolism, preventing the aging-dependent H 2 S reduction, and the elevation of the methyl donor, S-adenosylmethionine (SAM). Sirt6 downregulates Slc7a11 expression in an Sp1-dependent manner, decreasing cystine uptake and increasing Cgl H 2 S production activity. Additionally, comparative acetylome in old livers revealed Sirt6-related differential acetylation of most of the one-carbon enzymes. Specifically, Sirt6-dependent Matα1 K235 deacetylation reduces its SAM production activity and Cbs binding, thereby reducing its activation of Cbs-dependent H 2 S production. The net outcome is H 2 S and SAM levels as observed in young animals. Thus, we unveil a fundamental mechanism for the promotion of healthy longevity by Sirt6.